Triggered episodic vestibular syndrome and transient loss of consciousness due to a retrostyloidal vagal schwannoma: a case report - Spiegelberg, Maritta; Ermiş, Ekin; Raabe, Andreas; Tarnutzer, Alexander Andrea (Frontiers in Neurology, 2023)
Background: Various conditions may trigger episodic vertigo or dizziness, with positional changes being the most frequently identified condition. Here we describe a rare case of triggered episodic vestibular syndrome (EVS) accompanied by transient loss of consciousness (TLOC) linked to a retrostyloidal vagal schwannoma. Case description: A 27-yo women with known vestibular migraine presented with a 19-month history of nausea, dysphagia and odynophagia triggered by swallowing food and followed by recurrent TLOC. These symptoms occurred independently of her body-position, resulted in a weight loss of 10 kg within 1 year and in an inability to work. An extensive cardiologic diagnostic work-up undertaken before she presented to the neurologic department was normal. On fiberoptic endoscopic evaluation of swallowing she showed a decreased sensitivity and a slight bulging of the right lateral pharyngeal wall and a pathological pharyngeal squeeze maneuver without any further functional deficits. Quantitative vestibular testing revealed an intact peripheral-vestibular function, an electroencephalography was read as normal. On brain MRI, a 16x15x12 mm lesion in the right retrostyloidal space suspicious of a vagal schwannoma was detected. Radiosurgery was preferred over surgical resection, as resection of tumors in the retrostyloid space bears the risk of intraoperative complications and may result in significant morbidity. A single radiosurgical procedure (stereotactic CyberKnife radiosurgery, 1x13Gy) accompanied by oral steroids was performed. On follow-up, a cessation of (pre)syncopes was noted 6 months after treatment. Only residual infrequent episodes of mild nausea triggered by swallowing solid food remained. Brain MRI after 6 months demonstrated no progression of the lesion. In contrast, migraine headaches associated with dizziness remained frequent. Discussion: Distinguishing triggered and spontaneous EVS is important and identifying specific triggers by structured history taking is essential. Episodes being elicited by swallowing solid foods and accompanied by (near) TLOC should initiate a thorough search for a vagal schwannoma, as symptoms are often disabling and targeted treatment is available. In the case presented here, cessation of (pre)syncopes and significant reduction of nausea triggered by swallowing was noted with a 6-month delay, illustrating the advantages (no surgical complications) and disadvantages (delayed treatment response) of first-line radiotherapy in vagal-schwannoma treatment.